Scenario-Based Life Cycle Assessment of an Automotive Wire Harness - Funk, Felix; Nguyen, Huong Giang; Franke, Jörg (Sustainable Manufacturing as a Driver for Growth. Proceedings of the 19th Global Conference on Sustainable Manufacturing, December 4–6, 2023, Buenos Aires, Argentina, 2025)
Wire harnesses are one of the the largest purchased part for many automotive Original Equipment Manufacturers (OEMs). They are highly complex assembly products, consisting of hundreds of wires, electrical connectors, electronic parts, and ancillary materials such as tape. Assembly still is a largely manual process, as the complexity of the wire handling and low level of standardization and digitization pose a challenge to automation efforts. Wire harnesses are expected to increase in complexity and size due to current developments in the automotive sector, namely electromobility, autonomous driving, and digitalization. As a result, the importance of these products to the overall environmental impact of vehicles is likely to increase, with copper playing a significant role. In this study, the environmental impacts of a rear door wire harness are quantified by performing a Life Cycle Assessment (LCA), considering the life cycle from cradle to gate and based on different supply chain scenarios. The impact of sourcing and transport is shown and potential for improvement is derived, especially with regard to reshoring and automation.
CRIS-Team Scopus Importer:2025-02-28
Keywords: LCA; reshoring; supply chain; sustainability; wire harness